Russian roulette - Horowitz, Anthony (New York, New York : Puffin Books, an imprint of Penguin Group (USA), 2014)
"Alex Rider's life changed forever with one bullet. And it was cold-blooded killer Yassen Gregorovich who pulled the trigger, thrusting the fourteen-year-old Alex into the world of international espionage. Now, as Yassen receives his final orders to kill Alex, the mortal enemies must come face-to-face once agian. But what turned Yassen into such a ruthless assassin? What led him down such a darkened path? In some ways, Alex and Yassen are mirror images of each other. One chose to be a hero. The other chose evil. This is Yassen's story. The journey of the darkened path."--
"the story of an assassin" -- cover.
Includes excerpt from "Stormbreaker" and the short story "London Down."
Keywords: Assassins -- Juvenile fiction; Orphans -- Juvenile fiction; Adventure stories; Russia (Federation) -- History -- 1991- -- Juvenile fiction